Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2215/cjn.00560112
|View full text |Cite
|
Sign up to set email alerts
|

A Woman with Recurrent Calcium Phosphate Kidney Stones

Abstract: SummaryKidney stones composed predominantly (50% or more) of calcium phosphate constitute up to 10% of all stones and 15%-20% of calcium stones, 80% of which are composed of calcium oxalate. Calcium phosphate is a minor component of up to 30% of calcium oxalate stones as well. The cause of calcium phosphate stones is often obscure but most often related to a high urine pH. Some patients with calcium phosphate stones may have incomplete renal tubular acidosis. Others have distal renal tubular acidosis character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…[8][9][10][11][12][13] However, no prospective controlled studies in humans have shown the efficacy of K-cit in preventing recurrent CaP stone formation. 23 Citrate has a complex effect on urine solute excretion, and its effect on urine supersaturation with respect to CaP stone formation is difficult to predict. Some studies have shown that CaOx stones may transform into CaP stones over time, and use of citrate therapy may explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] However, no prospective controlled studies in humans have shown the efficacy of K-cit in preventing recurrent CaP stone formation. 23 Citrate has a complex effect on urine solute excretion, and its effect on urine supersaturation with respect to CaP stone formation is difficult to predict. Some studies have shown that CaOx stones may transform into CaP stones over time, and use of citrate therapy may explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…No prospective controlled trial has studied the effectiveness of citrate in reducing stone formation specifically in patients with CaP stones, and this remains an important clinical question. 23 Because CaP stone formers are characterized by alkaline urine compared with CaOx stone formers, the effect of citrate on CaP supersaturation and stone formation are difficult to predict. The alkali load would increase urine pH, increasing CaP supersaturation, whereas an increase in citrate and reduction in urinary calcium would lower CaP supersaturation; however, the net effect is uncertain.…”
mentioning
confidence: 99%
“…12,13 According to literature, our case had a history of urinary stone disease. Furthermore, ultrasound scan revealed destruction of renal parenchyma as a result of recurrent renal stones and hydronephrosis.…”
Section: Discussionmentioning
confidence: 92%
“…In light of our findings, acetazolamide should be administered with caution and justification. If deemed necessary to continue acetazolamide after initial stone occurrence, one might consider periodic ultrasound examinations, diet management, prophylactic urinary pH adjustments if indicated, and nephrological consultation (21,22).…”
Section: Discussionmentioning
confidence: 99%